2016
DOI: 10.1136/bmjopen-2015-009257
|View full text |Cite
|
Sign up to set email alerts
|

Comparing sutures versus staples for skin closure after orthopaedic surgery: systematic review and meta-analysis

Abstract: ObjectiveTo determine whether there still remains a significant advantage in the use of sutures to staples for orthopaedic skin closure in adult patients.DesignSystematic Review/ Meta-Analysis.Data sourcesMEDLINE-OVID, EMBASE-OVID, CINAHL and Cochrane Library. Grey and unpublished literature was also explored by searching: International Clinical Trial Registry, Grey Matters BIOSIS Previews, Networked Digital Library of Theses and Dissertations, ClinicalTrials.gov, UK Clinical Trials Gateway, UK Clinical Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 28 publications
4
80
1
Order By: Relevance
“…Current literature has reported a relationship between inflammatory bowel disease and use of chronic steroids with an increased risk for SSI, however, our results do not highlight this association. Lastly, Dermabond, although vastly preferred by patients has been anecdotally avoided in colorectal surgery given its perceived risk for increased SSI rates, however, we did not find an elevated infection risk when compared to the standard use of staples on multivariate analysis …”
Section: Discussioncontrasting
confidence: 53%
“…Current literature has reported a relationship between inflammatory bowel disease and use of chronic steroids with an increased risk for SSI, however, our results do not highlight this association. Lastly, Dermabond, although vastly preferred by patients has been anecdotally avoided in colorectal surgery given its perceived risk for increased SSI rates, however, we did not find an elevated infection risk when compared to the standard use of staples on multivariate analysis …”
Section: Discussioncontrasting
confidence: 53%
“…1 More recently, Krishnan et al performed a meta-analysis concluding that the only significant difference between staples and sutures was that staples reduced the closure time. 2 However, they believed that their results lent support to the Smith et al conclusion that clips have a higher infection rate in hip surgery than sutures. Both articles concluded that large, well-powered randomised controlled trials were necessary to determine the method of skin closure with the lowest complication rate.…”
mentioning
confidence: 77%
“…The optimal goal of skin closure “is to promote rapid skin healing and an acceptable cosmetic result while minimising the risk of dehiscence or infection” . More recently, Krishnan et al performed a meta‐analysis concluding that the only significant difference between staples and sutures was that staples reduced the closure time . However, they believed that their results lent support to the Smith et al conclusion that clips have a higher infection rate in hip surgery than sutures.…”
Section: Introductionmentioning
confidence: 99%
“…In orthopaedic and trauma surgery, staples and sutures are most frequently used as wound-closing material. A systematic review and metaanalysis reported no significant difference between materials [119]. In both cases, the authors noted significant methodological limitations of included studies.…”
Section: Surgical Debridement and Irrigationmentioning
confidence: 93%
“…In both cases, the authors noted significant methodological limitations of included studies. Again, none of these studies was performed in a trauma population, and there is an urgent need for well-designed randomised controlled trials comparing both materials [119,120]. The WHO does not make any recommendations regarding the type of material; however, when sutures are used, they suggest using triclosan-coated sutures for preventing SSIs.…”
Section: Surgical Debridement and Irrigationmentioning
confidence: 99%